2017
DOI: 10.1515/biolog-2017-0076
|View full text |Cite
|
Sign up to set email alerts
|

Forensic application of EST-derived STR markers in opium poppy

Abstract: Discrimination study in opium poppy (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
5
2
Order By: Relevance
“…In contrast, our study and others analyzed varieties bred by man and they cannot be considered as a population of randomly mating individuals by any means and many varieties could share a substantial portion of their genomes due to their origin, breeding history, and pedigree. This is the reason why we disagree with the argumentation in [23] and, despite the very low p-values for a random match in our case, we regard such values as uninformative and, thus, the obtained result leads us to have doubts about the system's robustness and to call for a higher number of markers. The last interesting outcome from multivariate analysis showed that there were differences between accessions of the same variety, such as Bergam, Maraton, Opal, or Orel (Figure 1a).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast, our study and others analyzed varieties bred by man and they cannot be considered as a population of randomly mating individuals by any means and many varieties could share a substantial portion of their genomes due to their origin, breeding history, and pedigree. This is the reason why we disagree with the argumentation in [23] and, despite the very low p-values for a random match in our case, we regard such values as uninformative and, thus, the obtained result leads us to have doubts about the system's robustness and to call for a higher number of markers. The last interesting outcome from multivariate analysis showed that there were differences between accessions of the same variety, such as Bergam, Maraton, Opal, or Orel (Figure 1a).…”
Section: Discussioncontrasting
confidence: 99%
“…This result suggests that the gene pool actually used for new varieties is quite narrow and/or that our system lacks robustness, as it was implicated by the identity analysis (ID) paired comparison of varieties. Although we could argue that the probability of a random match is much lower (e.g., pID = 1.09 × 10 −16 ; Table S4) than the probability (pID = 1.04 × 10 −3 ) published by Mičianová et al [23], one should treat such values carefully and also look behind the numbers to see their meaning. Such estimators were developed for application in forensic genetics or studies of wild populations and calculate the probability of a random match within an idealized population according to the Hardy-Weinberg law and other assumptions (see more about the topic in [51,52]).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Falsification is also a serious problem in the production of vegetable oils, especially the more expensive ones, including poppy seed oil. Chemical analyses of oils are used to determine the species origin of oil [ 17 ], but DNA analyses are appropriate to determine species origin and also the cultivar origin [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%